Gambaran Pelaksanaan Kewaspadaan Universal di Puskesmas Paniki Bawah Kecamatan Mapanget - Berhitu, Fergina Stefany; Sapulete, Margareth R.; Ottay, Ronald; Porajow, Zwingly Christian J.G. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
Universal Precautions is simple effective ways designed to protect healthcare workers and patients from infection of various pathogens. The purpose of this study is to describe the implementation of universal precautions in health centers of Paniki Bawah, Mapanget District of Manado City. This descriptive study has been conducted in October 2012 - December 2012 and sampling by using the total population method.The study results showed that all of the respondents wash their hands with soap, 6.67% respondents do not always wash their hands before contact with patients, all of the respondents wash their hands after contact with patients, (100%) of the respondents always wash hands when exposed to blood or body fluids, (3.33%) of respondents did not use sterile gloves when contact with blood or body fluids, (3.33%) of respondents did not use gloves when cleaning medical equipment, (10% ) of respondents did not always wear a mask when treating patients with suspected TB, (100%) of respondents always perform decontamination and sterilization procedures for medical equipment, (100%) of respondents said yes to the container waterproof and resistant to punctures, (100%) respondents always discard needles / sharps in the container, (100%) respondents said there were bins of medical and non-medical (100%) of the respondents dispose of medical waste and nonmedical according to the space provided. Keywords: Universal Precautions